A Comparative Study: Australian English and Indonesian Complimenting Behaviours - Atik Yuliyani (IJEE (Indonesian Journal of English Education), 2016)
ABSTRACT The present study investigates the similarities and differences between Australian English and Indonesian speakers on paying compliments. A total of 50 university-student informants participated in the study: 25 Indonesian native speakers and 25 Australian English native speakers. The data were collected through a written Discourse Completion Task (DCT) which consists of eight situational settings. The results showed some similarities and differences between Australian English and Indonesian speakers on paying compliment. The similarities included the fact that ability was the most frequently preferred topic for both Indonesians and Australians, both Indonesians and Australians were more likely to give explicit verbal compliment, and compliments occurred mostly from males to females. The differences were: firstly, Australians used implicit compliment as their second preference, while Indonesians used ‘no-response’ type. Secondly, Australian females gave more explicit verbal compliment than the males did, whereas Indonesian females and males gave almost equal amount of explicit verbal compliment. Thirdly, the second most frequent positive semantic carriers were adverbs in Indonesian, but verbs in Australian English. ABSTRAK Penelitian ini menyelidiki persamaan dan perbedaan antara Australia dan Indonesia dalam memberikan pujian. Sebanyak lima puluh mahasiswa yang terdiri dari 25 mahasiswa Australia dan 25 mahasiswa Indonesia terlibat dalam penelitian ini sebagai informan. Data dikumpulkan melalui instrument tertulis (DCT) yang terdiri dari delapan seting. Hasil penelitian menunjukkan beberapa persamaan dan perbedaan antara Australia dan Indonesia dalam memberikan pujian. Persamaannya meliputi kemampuan (ability) menjadi topik yang paling disukai oleh keduanya, baik Indonesia dan Australia lebih senang memberikan pujian lisan secara eksplisit, dan pujian terjadi sebagian besar dari laki-laki ke perempuan. Adapun perbedaannya antara lain: pertama, Australia menggunakan pujian implicit sebagai preferensi kedua sementara Indonesia menggunakan tipe ‘no response’. Kedua, wanita Australia memberi pujian lisan secara eksplisit lebih daripada laki-laki lakukan, sedangkan wanita dan pria Indonesia memberi jumlah yang hampir sama dari pujian lisan eksplisit. Ketiga, kata keterangan (adverbs) menjadi ungkapan semantik positif kedua yang digunakan Indonesia, sedangkan Australia menggunakan kata kerja (verbs) sebagai ungkapan semantik positif kedua. How to Cite: Yuliani, A. (2016). A Comparative Study: Australian English and Indonesian Complimenting Behaviours. IJEE (Indonesian Journal of English Education), 3(1), 15-28. doi:10.15408/ijee.v3i1.3940 Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i1.3940